2006
DOI: 10.1016/j.appet.2006.01.019
|View full text |Cite
|
Sign up to set email alerts
|

‘Finish your soup’: Counterproductive effects of pressuring children to eat on intake and affect

Abstract: The authors examined whether pressuring preschoolers to eat would affect food intake and preferences, using a repeated-measures experimental design. In the experimental condition, children were pressured to eat by a request to finish their food. We collected intake data, heights and weights, child-feeding practices data, and children's comments about the food. Children consumed significantly more food when they were not pressured to eat and they made overwhelmingly fewer negative comments. Children who were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
345
1
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(399 citation statements)
references
References 18 publications
20
345
1
19
Order By: Relevance
“…Consumption of disliked products, such as vegetables, may need some pressure, whereas liked products, such as fruits, may not need pressure. Variation in product liking may partly explain the different results in the literature regarding intake and pressuring strategies (13,16,18,20) . Parental intake and the PCF strategy 'Choice' were the strongest positive predictors of children's intake for both fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of disliked products, such as vegetables, may need some pressure, whereas liked products, such as fruits, may not need pressure. Variation in product liking may partly explain the different results in the literature regarding intake and pressuring strategies (13,16,18,20) . Parental intake and the PCF strategy 'Choice' were the strongest positive predictors of children's intake for both fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Restricting the intake of unhealthy food and giving health information about a product appear to foster an unhealthy eating pattern (11)(12)(13)(14) . Pressuring a child to eat and offering rewards using instrumental eating ('If you eat your spinach, you will get a dessert') also decrease children's intake or preferences (9,13,15,16) . However, the consequences of these strategies appear to be less straightforward, since pressure and reward may have positive effects under appropriate circumstances (17)(18)(19)(20) .…”
mentioning
confidence: 99%
“…Pressure to eat has been associated with increased neophobia (Fisher, Mitchell, Smiciklas-Wright, & Birch, 2002;Wardle et al, 2005; but see Bourcier, Bowen, Meischke, & Moinpour, 2003, for contrary evidence), food avoidance (Powell, Farrow, & Meyer, 2011), decreased liking for and consumption of the to-beeaten food (Galloway et al, 2005;Galloway, Fiorito, Francis, & Birch, 2006) and lower child BMI (in 6-8 year olds, Lee & Keller, 2012;at age 2, Farrow & Blissett, 2008). Indeed, retrospective reports have found that adults' food dislikes can be traced back to negative experiences involving pressure to eat (Batsell, Brown, Ansfield, & Paschall, 2002) and enjoyment of eating is predicted by less pressure to eat (Webber, Cooke, Hill, & Wardle, 2010).…”
Section: Coercive Feeding Practicesmentioning
confidence: 99%
“…Maladaptive feeding practices often derive from a parent's anxiety about the health and wellbeing of their child; the belief that their child is unable to selfregulate (Tan & Holub, 2011), is perceived to be underweight (Galloway et al, 2006) or overweight (Gregory, Paxton, & Brozovic, 2010a), or over responsive to food (Gregory, Paxton, & Brozovic, 2010b and/or when children's patterns of acceptance and rejection are not consistent with requirements for a balanced diet and healthy weight and growth (Dennison, 1996;Fisher & Kral, 2008;Pugliese et al, 1987), interventions are required which provide the necessary information and support to address this discrepancy.…”
Section: Parent-focussed Interventions For Non-clinical Feeding Diffimentioning
confidence: 99%
“…Such work includes the work of Birch on learning and peer modelling, and highlights the importance of the eating environment and the social nature of food, in which children are heavily influenced by their peers and those around them, as well as through learning by experience (Birch, 1980(Birch, , 1990. For example, recent research suggests that if parents or caregivers pressure their children to eat more food, then children are conversely likely to eat less (Galloway, Fiorito, Francis, & Birch, 2006). This particular study, however, examined children's behaviour in an experimental situation at school, rather than examining the complexity of everyday eating practices within the home (cf.…”
Section: Psychology: Satiety and Parental Feeding Practicesmentioning
confidence: 99%